2014
DOI: 10.1260/1747-9541.9.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy-Supportive Pedagogical Approach to Sports Coaching: Research, Challenges and Opportunities

Abstract: There has been an increasing body of research on autonomy- or need-support specific to a coaching context that warrants some review of what we know and don't know, and what might be generative for future research. The previous studies reviewed within this article have shown consistent support for Self-determination theory with autonomy-supportive environments linked with adaptive outcomes, such as superior performance, enhanced self-worth, increased effort, and self-determined motivation; while controlling env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 44 publications
4
58
0
Order By: Relevance
“…This analysis demonstrated common practices amongst the coaches that were not only consistent with TDE research (Henriksen, et al, 2011;Martindale et al, 2007;Mills et al, 2012), research of successful high performance coaches (Lara-Bercial & Mallett, 2016) but also consistent with motivationally adaptive climates. The coaches all created a more empowering and less disempowering climate, which is consistent with the International Sport Coaching Framework (ICCE, 2013), findings from Smith et al's (2016) large scale study of youth sport coaches, and associated with motivationally adaptive outcomes for participants (e.g., Gilchrist & Mallett, 2017;Harwood, et al, 2015;Occhino et al, 2014). In addition, respondents in the current study indicated that coaches exhibited transformational leadership behaviours which have also been associated with desired outcomes for participants (e.g., Callow et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This analysis demonstrated common practices amongst the coaches that were not only consistent with TDE research (Henriksen, et al, 2011;Martindale et al, 2007;Mills et al, 2012), research of successful high performance coaches (Lara-Bercial & Mallett, 2016) but also consistent with motivationally adaptive climates. The coaches all created a more empowering and less disempowering climate, which is consistent with the International Sport Coaching Framework (ICCE, 2013), findings from Smith et al's (2016) large scale study of youth sport coaches, and associated with motivationally adaptive outcomes for participants (e.g., Gilchrist & Mallett, 2017;Harwood, et al, 2015;Occhino et al, 2014). In addition, respondents in the current study indicated that coaches exhibited transformational leadership behaviours which have also been associated with desired outcomes for participants (e.g., Callow et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
“…Two theories have been prominent in conceptualizing the motivational climate, achievement goal theory (AGT) (Nicholls, 1989) and self-determination theory (SDT) (Ryan & Deci, 2000) (for reviews see Gilchrist & Mallett, 2017;Harwood, Keegan, Smith, & Raine, 2015;Occhino, Mallett, Rynne, & Carlisle, 2014). AGT focuses on how ability is understood in a given context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there is a need to increase awareness about the complexity, and number of challenges, in promoting an empowering style of sports coaching in the real-world of youth sport (e.g., Denison, Mills, & Konoval, 2017;Kidman, 2001;Occhino, Mallett, Rynne, & Carlisle, 2014;Solstad et al, 2017). Over the past few years, only a small number of studies have actually highlighted that a behavioral shift to becoming an empowering sports coach is related to aspects, such as youth sport coaches' levels of self-awareness (Smith, 2014), sports coaching's disciplinary legacy (Denison et al, 2017), the contrasts between the content of CDPs and the realities of everyday coaching practices (Stodter & Cushion, 2014), the individual-based nature of current CDPs , and the lack of research examining the challenges of shifting from one style of sports coaching to another (Occhino et al, 2014).…”
Section: Practical Implications and Future Researchmentioning
confidence: 99%
“…Over the past few years, only a small number of studies have actually highlighted that a behavioral shift to becoming an empowering sports coach is related to aspects, such as youth sport coaches' levels of self-awareness (Smith, 2014), sports coaching's disciplinary legacy (Denison et al, 2017), the contrasts between the content of CDPs and the realities of everyday coaching practices (Stodter & Cushion, 2014), the individual-based nature of current CDPs , and the lack of research examining the challenges of shifting from one style of sports coaching to another (Occhino et al, 2014). Conversely, the majority of studies in the field of sport psychology have only reported the benefits of an empowering style of sports coaching, without acknowledging the difficult aspects related to coach education pedagogy and, ultimately, behavioral change (e.g., Duda, 2013;Duda & Appleton, 2016).…”
Section: Practical Implications and Future Researchmentioning
confidence: 99%